Differential response of adipose tissue gene and protein expressions to 4‐ and 8‐week administration of β‐guanidinopropionic acid in mice. Issue 5 (7th March 2018) - Kato, Hisashi; Masuda, Shinya; Ohira, Tomotaka; Ohira, Luna; Takakura, Hisashi; Ohira, Yoshinobu; Izawa, Tetsuya
Abstract: β ‐Guanidinopropionic acid ( β ‐GPA) feeding inhibits growth‐associated gain of body mass. It remains unknown, however, whether and how β ‐GPA feeding affects growth‐associated increase in white adipose tissue (WAT) mass. We examined the effects of 4‐ and 8‐week β ‐GPA feeding on serum myostatin levels and expression of genes and proteins related to adipogenesis, lipolysis, and liposynthesis in epididymal WAT (eWAT) and brown adipose tissue (BAT) in 3‐week‐old, juvenile male mice. Body, eWAT, and muscle weights were significantly lower in β ‐GPA‐fed mice than in controls after feeding. Four‐ but not 8‐week‐ β ‐GPA feeding increased the serum myostatin level. Incubation of C2C12 myotubes with β ‐GPA (1 mM) significantly promoted myostatin mRNA expression. The protein expression of peroxisome proliferator‐activated receptor gamma coactivator 1 α (PGC‐1 α ) and peroxisome proliferator‐activated receptor α (PPAR α ) was up‐regulated in GPAF eWAT at week 4, but down‐regulated at week 8. There was no significant difference in the protein expression of adipocyte triglyceride lipase (ATGL), hormone‐sensitive lipase (HSL), fatty acid synthase (FAS), and acetyl‐CoA carboxylase (ACC) between groups in eWAT. In BAT, no significant difference was found in the protein expression of PGC‐1 α, PPAR α, ATGL, and HSL between β ‐GPA‐fed and control mice, whereas that of FAS and ACC was significantly lower in β ‐GPA‐fed mice at week 8. Uncoupling protein 1 was expressed higher in β ‐GPA‐fed mice both at weeks 4 and 8 than that in controls. Thus, the mechanism by which β ‐GPA feeding in early juvenile mice inhibits growth‐associated increase in eWAT mass may differ between early and later periods of growth. Abstract : In this study, we examined the effects of oral administration of β‐guanidinopropionic acid (β‐GPA) on white adipose tissue (WAT) and brown adipose tissue (BAT) mass and on the expression of genes and proteins involved in controlling fatty acid oxidation, lipid synthesis, and adipogenesis. The results demonstrated that the protein expression of peroxisome proliferator‐activated receptor gamma coactivator 1 α (PGC‐1α) and peroxisome proliferator‐activated receptor α (PGC‐1α) was upregulated in WAT after 4‐ but not 8‐week β‐GPA supplementation compared to controls. Furthermore, in BAT, no significant difference was found in the protein expression of PGC‐1α and PPARα between β‐GPA‐fed and control mice, whereas uncoupling protein 1 was expressed higher in β‐GPA‐fed mice both at weeks 4 and 8 than that in controls.